The SSTARS (STeroids and Stents Against Re-Stenosis) Trial: Different stent alloys and the use of peri-procedural oral corticosteroids to prevent in-segment restenosis after percutaneous coronary intervention. (1st August 2016) - Adam, Z.; Turley, A.; Mason, J.M.; Kasim, A.S.; Newby, D.; Mills, N.; Padfield, G.; Thompson, L.; Morley, R.; Hall, J.A.; Wright, R.A.; Muir, D.F.; et al.
Abstract: Background: Stent design and technological modifications to allow for anti-proliferative drug elution influence restenosis rates following percutaneous coronary intervention (PCI). We aimed to investigate whether peri-procedural administration of corticosteroids or the use of thinner strut cobalt alloy stents would reduce rates of binary angiographic restenosis (BAR) after PCI. Methods: This was a two centre, mixed single and double blinded, randomised controlled trial using a factorial design. We compared (a) the use of prednisolone to placebo, starting at least six hours pre-PCI and continued for 28 days post-PCI, and (b) cobalt chromium (CoCr) to stainless steel (SS) alloy stents, in patients admitted for PCI. The primary end-point was BAR at six months. Results: 315 patients (359 lesions) were randomly assigned to either placebo (n = 145) or prednisolone (n = 170) and SS (n = 160) or CoCr (n = 160). The majority (58%) presented with an ACS, 11% had diabetes and 287 (91%) completed angiographic follow up. BAR occurred in 26 cases in the placebo group (19.7%) versus 31 cases in the prednisolone group (20.0%) respectively, p = 1.00. For the comparison between SS and CoCr stents, BAR occurred in 32 patients (21.6%) versus 25 patients (18.0%) respectively, p = 0.46. Conclusion: Our study showed that treating patients with a moderately high dose of prednisolone for 28 days following PCI with BMS did not reduce the incidence of BAR. In addition, we showed no significant reduction in 6 month restenosis rates with stents composed of CoCr alloy compared to SS (http://www.isrctn.com/ISRCTN05886349 ).